ANALISIS KOMUNITAS ONLINE RELIGI KSATRIAK2I.GRAM - perdana, samuel (Jurnal Dinamika Sosial Budaya, 2022)
In the era of industry 4.0 as it is today, technology is rampant and has affected various aspects of life, including the way we communicate. Nowadays, the community does not have to do conventional methods, such as direct contact and doing kopdar or ground coffee once a week. A community can be born and develop online on various social media platforms. The community that we discuss in this journal is the religious community of knights2i.gram which was born on Instagram and already has more than 3 thousand followers and 300 people in its discord and wa groups. This community is engaged in the field of Christianity and fights for the rights of Christians as a minority community in Indonesia. This is a challenge for us because we analyze an online-based community as we are curious about how this community can develop while the members and the management have never met in person.